2021
DOI: 10.1016/j.envc.2021.100215
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 and PM10 during COVID-19 lockdown in Kuwait: Mixed effect of dust and meteorological covariates

Abstract: This study investigated the impact of COVID-19 lockdown on particulate matter concentrations, specifically PM 2.5 and PM 10 , in Kuwait. We studied the variations in PM 2.5 and PM 10 between the lockdown in 2020 with the corresponding periods of the years 2017–2019, and also investigated the differences in PM variations between the ‘curfew’ and ‘non curfew’ hours. We applied mixed-effect regression to investigate the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…To investigate the results obtained by the previous study (Ghanim 2022 ), excellent research has been conducted in the United Arab Emirates (Mansouri Daneshvar et al 2022 ) that studied how COVID-19 reduces pollution at the local scale of the country. As a result, this study and others have also found that SARS-CoV-2 lockdown reduces air pollution levels in MENA nations including Morocco, Kuwait, Tunisia, Qatar, and Iraq (Khomsi et al 2020 ; Al-Hemoud et al 2021 ; Jribi et al 2020 ; Mahmoud et al 2022 ; Hashim et al 2021a , b ).…”
Section: Thematic Discussionsupporting
confidence: 58%
“…To investigate the results obtained by the previous study (Ghanim 2022 ), excellent research has been conducted in the United Arab Emirates (Mansouri Daneshvar et al 2022 ) that studied how COVID-19 reduces pollution at the local scale of the country. As a result, this study and others have also found that SARS-CoV-2 lockdown reduces air pollution levels in MENA nations including Morocco, Kuwait, Tunisia, Qatar, and Iraq (Khomsi et al 2020 ; Al-Hemoud et al 2021 ; Jribi et al 2020 ; Mahmoud et al 2022 ; Hashim et al 2021a , b ).…”
Section: Thematic Discussionsupporting
confidence: 58%
“…In addition, a modeling technique such as a mixed-effect regression model may further explain the variation of PM2.5 as it allows both fixed and random effects in the model. The changes in PM2.5 due to other pollutants and meteorological factors could be determined using a mixed-effect regression model which provides a better understanding of the effect of meteorological parameters and pollutants on PM concentrations (Al-Hemoud et al, 2021).…”
Section: The Relationship Between Air Contaminants and Weather Conditionsmentioning
confidence: 99%
“…The highest PM 2.5 concentration occurred in winter during the day. It has been shown that the PM 2.5 concentration is positively correlated with relative humidity [ 36 ]. In summer, the relative humidity at night is significantly higher during the day, and during the sampling period, the average wind speed at night in Lanzhou was low (1.16 m/s).…”
Section: Resultsmentioning
confidence: 99%